Signaling and Counter‐Signaling in the Judicial Hierarchy: An Empirical Analysis of En Banc Review. Issue 2 (6th July 2015) - Beim, Deborah; Hirsch, Alexander V.; Kastellec, Jonathan P.
Abstract : We leverage the institutional features of American courts to evaluate the importance of whistleblowers in hierarchical oversight. Drawing on a formal theory of signaling in the judicial hierarchy, we examine the role of whistleblowing dissents in triggering en banc review of three‐judge panels by full circuits of the Courts of Appeals. The theory generates predictions about how dissent interacts with judicial preferences to influence circuits' review and reversal decisions, which we test using original and existing data. First, we show that judges who dissent counter to their preferences are more likely to see their dissents lead to review and reversal. Second, we show that dissents are most influential when the likelihood of non‐compliance by a three‐judge panel is highest. Our results underscore the importance of dissent in the judicial hierarchy and illustrate how judicial whistleblowers can help appellate courts target the most important cases for review.